An unsuspected role for organic cation transporter 3 in the actions of amphetamine. (November 2018) - Mayer, Felix; Schmid, Diethart; Owens, W.; Gould, Georgianna; Apuschkin, Mia; Kudlacek, Oliver; Salzer, Isabella; Boehm, Stefan; Chiba, Peter; Williams, Piper; Wu, Hsiao-Huei; Gether, Ulrik; et al.
Abstract Amphetamine abuse is a major public health concern for which there is currently no effective treatment. To develop effective treatments, the mechanisms by which amphetamine produces its abuse-related effects need to be fully understood. It is well known that amphetamine exerts its actions by targeting high-affinity transporters for monoamines, in particular the cocaine-sensitive dopamine transporter. Organic cation transporter 3 (OCT3) has recently been found to play an important role in regulating monoamine signaling. However, whether OCT3 contributes to the actions of amphetamine is unclear. We found that OCT3 is expressed in dopamine neurons. Then, applying a combination of in vivo, ex vivo, and in vitro approaches, we revealed that a substantial component of amphetamine's actions is OCT3-dependent and cocaine insensitive. Our findings support OCT3 as a new player in the actions of amphetamine and encourage investigation of this transporter as a potential new target for the treatment of psychostimulant abuse.